Wpływ czasowego zaangażowania w media społecznościowe młodych dorosłych na zachowania związane z wyglądem ciała - Leksy, Karina (Studia Edukacyjne, 2022)
Social media have become a part of people’s lives, being not only a place of entertainment and mutual communication but also promotion of pop culture models connected with the human body appearance. For many, these models become guidelines for behaviors regarding body looks and a source for its assessment by comparing their appearance to that of models. The purpose of this article is to present the correlation between the amount of time spent by young adult respondents in the social media space and modelling themselves on other people as regards the appearance, comparing their own bodies to other users’ bodies and patterns of behavior to improve the body look. A diagnostic survey method was applied in the study and the author’s questionnaire in an online form was used. 493 young adults, social networks users, participated in the study. The results show that the more time the respondents spend on social media, the more they model themselves on others as regards their physical appearance, the more often they compare the look of their bodies with those of other people and undertake more behaviors targeted at improving their appearance. The specified correlations refer to a greater extent to the male subjects of the study. These results constitute an important guideline for prevention and educational activities concerning the significance of body looks in modern culture, including consequences of increasing social pressure on the image of the male body.